Smart Life Tech: smart Oku's parking / Nurul Shuhadah Jasri, Nurul Amirah Muhamad and Nur Amirah Ahman - Jasri, Nurul Shuhadah; Muhamad, Nurul Amirah; Ahman, Nur Amirah (2017)
Smart Life Tech is a Malaysia leader transportation industry in the design, research and development, management of parking technology. We will be transforming the parking experience and increasing revenues for a huge range of clients